A brief overview of the monitoring network for lakes in Greece (2023)
Kemitzoglou, D., A. Apostolakis, E. Mavromati, M. Seferlis, M. Skopa, E. Tsantila and V. Tsiaoussi. 2014. A brief overview of the monitoring network for lakes in Greece. p. 65 In: 15th World Lake Conference, Lakes: The mirrors of the earth, Perugia, Italy, 1-5/09/2014. (Book of abstracts)